The human species : - Relethford, John (McGraw-Hill, 2008)
This text introduces physical anthropology, the science of human biological evolution and variation. It addresses the major questions that concern biological anthropologists: "What are humans?" "How are we similar to and different from other animals?" "Where are our origins?" "How did we evolve?" "Are we still evolving?" "How are we different from one another?" and "What does the future hold for the human species?"